LRBA Deficiency Can Lead to Lethal Colitis That Is Diminished by SHIP1 Agonism - Sudan, Raki; Fernandes, Sandra; Srivastava, Neetu; Pedicone, Chiara; Meyer, Shea T.; Chisholm, John D.; Engelman, Robert W.; Kerr, William G. (Frontiers in Immunology, 2022)
Humans homozygous for inactivating LRBA (lipopolysaccharide (LPS)-responsive beige-like anchor) mutations or with compound heterozygous mutations exhibit a spectrum of immune-related pathologies including inflammatory bowel disease (IBD). The cause of this pathology remains undefined. Here we show that disruption of the colon epithelial barrier in LRBA-deficient mice by dextran sulfate sodium (DSS) consumption leads to severe and uniformly lethal colitis. Analysis of bone marrow (BM) chimeras showed that susceptibility to lethal colitis is primarily due to LRBA deficiency in the immune compartment and not the gut epithelium. Further dissection of the immune defect in LRBA-deficient hosts showed that LRBA is essential for the expression of CTLA4 by Treg cells and IL22 and IL17 expression by ILC3 cells in the large intestine when the gut epithelium is compromised by DSS. We further show that SHIP1 agonism partially abrogates the severity and lethality of DSS-mediated colitis. Our findings indicate that enteropathy induced by LRBA deficiency has multiple causes and that SHIP1 agonism can partially abrogate the inflammatory milieu in the gut of LRBA-deficient hosts.